A Numerical Analysis of Landslide Movements Considering the Erosion and Deposition along the Flow Path - Aminudin Syah; Teuku Faisal Fathani; Fikri Faris (Journal of the Civil Engineering Forum, 2019)
Landslides are one of the most frequent disasters which occur widespread in Indonesia. This disaster often causes damages and fatalities. One of the mitigations efforts to reduce potential loss is by predicting the area affected by landslide movement. This research developed a numerical model of landslide movement by incorporating the erosion and deposition laws along the flow path. This model improves the accuracy of the previous models which assume that landslide volume is constant without any consideration for the erosion and deposition. The governing equation of this newly developed model uses the Eulerian numerical approach based on the finite difference scheme. The erosion-deposition laws applied in this research are from Egashira et al. (2001), McDougall and Hungr (2005), and Blanc (2008). The simulation program applies Python programming language and examines an imaginary slope with ellipsoid-shaped of source area. The simulation result shows that the additional erosion-deposition formula can enlarge the volume and the affected area of landslide movement. It is clarified that the erosion rate is a determinant factor affecting the results of calculation.